On the identities of the molluscan names described in A Short Zoology of Tahiti in the Society Islands by Anthony Curtiss in 1938 (Mollusca: Cephalopoda, Gastropoda) - Low, Martyn E.y.; Tan, Siong Kiat (Zootaxa, 2014)
Anthony Curtiss described two species of cephalopod and nine species of gastropod molluscs from Tahiti. Herein, we discuss and determine the identities of these eleven names. Ten of these names are considered to be junior subjective synonyms of well-known taxa, and one an unavailable name.